2008
DOI: 10.1038/sj.bjc.6604277
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-necrosis factor-A polymorphisms and gastric cancer risk: a meta-analysis

Abstract: Inflammation is one of the early phases in the development of gastric cancer. Therefore, several studies have examined the association of polymorphisms in tumour-necrosis factor-A gene (TNF-A) with gastric cancer risk. This meta-analysis reviews and summarises published evidence for these associations. Searching several databases yielded 24 independent studies that reported on the associations between TNF-A polymorphisms and gastric cancer risk. We analysed available data for the most commonly investigated pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
65
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 49 publications
11
65
0
1
Order By: Relevance
“…As in our previous meta-analyses (Gorouhi et al, 2008;Islami and Kamangar, 2008), we present the results for larger studies, defined as those with s.e. p0.5 separately.…”
Section: Discussionmentioning
confidence: 99%
“…As in our previous meta-analyses (Gorouhi et al, 2008;Islami and Kamangar, 2008), we present the results for larger studies, defined as those with s.e. p0.5 separately.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of various genes, such as CDH1 (Humar et al, 2002), GSTT1 (Saadat, 2006), IL1RN (Rocha et al, 2005), MTHFR , TP53 (Zhou et al, 2007) and TNF-A (Gorouhi et al, 2008), have been shown to be associated with gastric cancer. Aside from these candidate genes, some recent studies suggest that polymorphisms in the miRNA genes may serve as novel risk predictors for gastric cancer.…”
Section: Dysregulated Mirnas In Gastric Cancermentioning
confidence: 99%
“…The TNFA-308G>A promoter SNP is one of the most frequently reported candidate host factors associated with the risk for gastric carcinoma. However, the increasing number of published studies has revealed a conspicuous lack of reproducibility among the various populations (23,24). So far, it is not known whether the TNFA-308G>A SNP is acting as an etiologic susceptibility locus or if it is associated in linkage disequilibrium with a causal sequence variant that has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Although several promoter polymorphisms have been analyzed, most studies have focused on the TNFA-308G>A (rs1800629). Since the first reports of TNFA association with gastric carcinoma (18)(19)(20)(21)(22), the TNFA-308*A allele has emerged as an important candidate accounting for the increased risk of gastric carcinoma development (23,24). Nevertheless, outcomes of the numerous studies on whether polymorphisms in or near TNF genes do underlie these associations are conflicting.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation